PENGGUNAAN UNGKAPAN JAWA DALAM KUMPULAN PUISI TIRTA KAMANDANU KARYA LINUS SURYADI (Pendekatan Stilistika Kultural) - Burhan Nurgiyantoro (LITERA, 2014)
This study aims to describe the intensity of the use of Javanese words and idioms inwayang poems. It employed the textual approach. The data sources were wayang poemsunder the subsection of “Lingga dan Yoni” in Tirta Kamandanu (1997), a poetry anthologyby Linus Suryadi. There were 26 poems all of which were studied. The steps includedlinguistic evidence collection, data display, and explanation of esthetic functions. Thestudy concludes that the use of Javanese words and idioms in wayang poems is intensiveenough. They are relevant to the meanings in the poems narrating wayang and supportand strengthen the meanings and existence of the Javanese culture. They also support thefunctions of poetry style beauty, especially the beauty of rhymes and particular atmospherecreation, are accurate in the condensed forms, and serve as fillers for emptiness or justsynonyms. Without knowledge and understanding of the Javanese culture, one will notunderstand the poems as well, thoroughly, and intensively as one who understands theJavanese cultural background.